Design and Analysis of a Laminar Diffusion-Based Micromixer with Microfluidic Chip - GİRİT, OĞUZ (HINDAWI LTD, 2021)
This study aims to perform optimizatione to achieve the best diffusion control between the channels by designing and analysing a microfluidic-based micromixer. The design and analysis of the micromixer were made with the COMSOL Multiphysics program. Some input and output parameters must be defined for diffusion control of the micromixer. Among these parameters, inputs are the diffusion coefficient and inlet flow rate, while outputs are velocity, pressure, and concentration. Each input parameter in the microfluidic chip affects the output of the system. To make the diffusion control in the most optimum way, the data were obtained by making much analysis. The data obtained from this program was also provided with the Fuzzy Logic method to optimize the microfluidic chip. The diffusion coefficient value (5E-11 m(2)/s) should be given to the channels to achieve the optimum diffusion between the micromixer channels, if the inlet flow rate value (15E-15 m(3)/s) is the output value of the system, the velocity is 0.09 mm/s. The pressure is 2 Pa, and the concentration is 0.45 mol/m(3). These values are the optimum values obtained from the analysis without damaging the liquid's microfluidic channels supplied to the micromixer's inlet.
Keywords: NUMERICAL-SIMULATION; HIGH-THROUGHPUT; SYSTEM; MIXER